Property impacts on Carbon Capture and Storage (CCS) processes: A review. (15th June 2016) - Tan, Yuting; Nookuea, Worrada; Li, Hailong; Thorin, Eva; Yan, Jinyue
Highlights: Property impacts on CCS processes have been reviewed. Properties were ranked and priority of properties in model development was analyzed. Relevant properties in the design and operation of CCS processes have been identified. The studied CCS processes include CO2 capture, conditioning, transport and storage. Abstract: The knowledge of thermodynamic and transport properties of CO2 -mixtures is important for designing and operating different processes in carbon capture and storage systems. A literature survey was conducted to review the impact of uncertainty in thermos-physical properties on the design and operation of components and processes involved in CO2 capture, conditioning, transport and storage. According to the existing studies on property impacts, liquid phase viscosity and diffusivity as well as gas phase diffusivity significantly impact the process simulation and absorber design for chemical absorption. Moreover, the phase equilibrium is important for regenerating energy estimation. For CO2 compression and pumping processes, thermos-physical properties have more obvious impacts on pumps than on compressors. Heat capacity, density, enthalpy and entropy are the most important properties in the pumping process, whereas the compression process is more sensitive to heat capacity and compressibility. In the condensation and liquefaction process, the impacts of density, enthalpy and entropy are low on heat exchangers. For the transport process, existing studies mainly focused on property impacts on the performance of pipeline steady flow processes. Among the properties, density and heat capacity are most important. In the storage process, density and viscosity have received the most attention in property impact studies and were regarded as the most important properties in terms of storage capacity and enhanced oil recovery rate. However, for physical absorption, physical adsorption and membrane separation, there has been a knowledge gap about the property impact. In addition, due to the lack of experimental data and process complexity, little information is available about the influence of liquid phase properties on the design of the absorber and desorber for chemical absorption process. In the CO2 conditioning process, knowledge of the impacts of properties beyond density and enthalpy is insufficient. In the transport process, greater attention should focus on property impacts on transient transport processes and ship transport systems. In the storage process, additional research is required on the dispersion process in enhanced oil recovery and the dissolution process in ocean and saline aquifer storage.